Techno-Economic Analysis of Biodiesel Production from Microalgae - Rendra Panca Anugraha; Adelia Melita Sari; Habib Nurrohim; Renanto Renanto; Juwari Juwari; Donny Satria Bhuana (Reaktor, 2026)
The increasing global energy demand and the urgent necessity to mitigate greenhouse gas emissions have driven the exploration of renewable energy alternatives to fossil-based fuels, such as biofuels derived from sustainable biological sources. Among various potential feedstocks, microalgae have gained considerable attention due to their high lipid productivity, rapid growth rate, and ability to utilize CO₂ efficiency through photosynthesis. This study presents the design and techno-economic evaluation of a biodiesel production plant utilizing Chlorella vulgaris microalgae as the primary feedstock. The cultivation process employs a Flat Plate Photobioreactor (FPPBR) system to enhance biomass productivity under controlled light and nutrient conditions. The production process adopts the Lurgi technology, beginning with the extraction of microalgae oil using n-hexane solvent, which is subsequently converted into biodiesel through esterification and transesterification reactions catalyzed by H₂SO₄ and NaOH, respectively. The designed plant capacity is 100,000 kL of biodiesel per year. Bontang, East Kalimantan, is selected as the plant site considering key factors such as raw material availability, access to utilities, land suitability, and transportation infrastructure. The plant consists of two main stages: microalgae oil production and biodiesel synthesis, with a total construction period of two years and an operational lifespan of 15 years. Economic feasibility analysis indicates an Internal Rate of Return (IRR) of 12.91%, a Net Present Value (NPV) of IDR 2,296,063,930,982, and a payback period of 13 years, confirming the financial viability of the project. These results demonstrate that biodiesel production from Chlorella vulgaris microalgae is both technically feasible and economically sustainable, providing a practical and scalable pathway to support Indonesia’s transition toward renewable and low-carbon energy systems.